2023
DOI: 10.3390/ijms241612725
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin (TSLP), Its Isoforms and the Interplay with the Epithelium in Allergy and Asthma

Abstract: Thymic stromal lymphopoietin (TSLP) is a pleiotropic cytokine that has emerged as a critical player in the development and progression of allergy and asthma. It is primarily produced by epithelial cells and functions as a potent immune system activator. TSLP acts through interaction with its receptor complex, composed of the TSLP receptor (TSLPR) and interleukin-7 receptor alpha chain (IL-7Rα), activating downstream complex signalling pathways. The TSLP major isoform, known as long-form TSLP (lfTSLP), is upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…They emphasized that the occurrence of asthma may be associated not with systemic TSLP secretion but with local secretion [8]. Similarly, Smolinska et al observed the impact of both TSLP genotype and expression in the nasal epithelium, rather than systemic TSLP, on the increased risk of asthma in children [32].…”
Section: Discussionmentioning
confidence: 99%
“…They emphasized that the occurrence of asthma may be associated not with systemic TSLP secretion but with local secretion [8]. Similarly, Smolinska et al observed the impact of both TSLP genotype and expression in the nasal epithelium, rather than systemic TSLP, on the increased risk of asthma in children [32].…”
Section: Discussionmentioning
confidence: 99%